Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №560

Упростите выражение:
а)
$(-x^2y^2)^4 * (-xy)^2$
;
б)
$-(\frac{1}{3}xy^3)^2 * (-3x)^3$
;
в)
$(-2x^3y^2)^3 * (-2y^2)^3$
;
г)
$(\frac{1}{3}a^2b)^3 * (9ab^2)^2$
;
д)
$(-5a^3b)^2 * (\frac{1}{5}ab^3)^3$
;
е)
$(-\frac{2}{7}ab^4)^2 * (-3\frac{1}{2}a^3b)^2$
;
ж)
$(x^3y)^2 * (-5xy)^3$
;
з)
$(\frac{1}{6}x^2y^2)^2 * (-12x^3y^5)^2$
.

Решение а

$(-x^2y^2)^4 * (-xy)^2 = x^8y^8 * x^2y^2 = x^{10}y^{10}$

Решение б

$-(\frac{1}{3}xy^3)^2 * (-3x)^3 = -\frac{1}{9}x^2y^6 * (-27x^3) = 3x^5y^6$

Решение в

$(-2x^3y^2)^3 * (-2y^2)^3 = -8x^9y^6 * (-8y^6) = 64x^9y^{12}$

Решение г

$(\frac{1}{3}a^2b)^3 * (9ab^2)^2 = \frac{1}{27}a^6b^3 * 81a^2b^4 = 3a^8b^7$

Решение д

$(-5a^3b)^2 * (\frac{1}{5}ab^3)^3 = 25a^6b^2 * \frac{1}{125}a^3b^9 = \frac{1}{5}a^9b^{11}$

Решение е

$(-\frac{2}{7}ab^4)^2 * (-3\frac{1}{2}a^3b)^2 = \frac{4}{49}a^2b^8 * (-\frac{7}{2}a^3b)^2 = \frac{4}{49}a^2b^8 * \frac{49}{4}a^6b^2 = a^8b^{10}$

Решение ж

$(x^3y)^2 * (-5xy)^3 = x^6y^2 * (-125x^3y^3) = -125x^9y^5$

Решение з

$(\frac{1}{6}x^2y^2)^2 * (-12x^3y^5)^2 = \frac{1}{36}x^4y^4 * 144x^6y^10 = 4x^{10}y^{14}$